Masjid sebagai sarana pemberdayaan ekonomi umat - Adnanda Yudha Rhealdi; Muthoifin; Rizka (Universitas Widya Mataram, 2023)
Community development by utilizing the mosque's financial circulation is one of the efforts to maximize the role and function of the mosque. Communities around the mosque are empowered economically through mosque activities. Al-Falah Grand Mosque is one of the mosques that has implemented economic empowerment activities for the people around the mosque. As a result, this mosque became a prosperous mosque and even became a national pilot mosque. The purpose of this research is to dissect the management strategy of Al-Falah Mosque in Sragen in empowering the people's economy. This type of research is qualitative research with a descriptive approach that utilizes case studies to analyze problems. Collecting data using interview techniques, observation and documentation. The research location is at Masjid Raya Al-Falah Sragen. This research resulted in an explanation of the strategy of the Al-Falah Mosque in Sragen in empowering the people's economy. Many kinds of activities are carried out for empowerment participants, ranging from religious studies, learning to read the Koran and tahsin qiro'ah, joint dhikr, distribution of basic necessities and other incidental training to make the Al-Falah Mosque's breadwinner community continue to grow.